2009
DOI: 10.1097/pep.0b013e3181beff38
|View full text |Cite
|
Sign up to set email alerts
|

A Core Stability Group Program for Children with Developmental Coordination Disorder: 3 Clinical Case Reports

Abstract: Physical activity promotion in this population has the potential to improve the quality of life and reduce health risks associated with sedentary lifestyles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 27 publications
4
22
0
5
Order By: Relevance
“…These findings were consistent with those of Kaufman and Schilling, 15 Kane and Bell 16 and Menz et al, 17 but not consistent with results of Granacher and Gollhofer, 18 Granacher et a l . , 19 a n d M c C u r d y a n d L a n g f o r d .…”
Section: The Effect Of Strength Training Based On Process Approach Insupporting
confidence: 83%
See 4 more Smart Citations
“…These findings were consistent with those of Kaufman and Schilling, 15 Kane and Bell 16 and Menz et al, 17 but not consistent with results of Granacher and Gollhofer, 18 Granacher et a l . , 19 a n d M c C u r d y a n d L a n g f o r d .…”
Section: The Effect Of Strength Training Based On Process Approach Insupporting
confidence: 83%
“…The results showed that strength training had no significant effect on dynamic balance in children with DCD. The results were consistent with findings of Bohannon 20 on patients referred to physiotherapy, Granacher and Gollhofer 18 and Granacher et al, 19 on prepubertal children but were not consistent with results of Kaufman and Schilling, 15 Kane and Bell, 16 Menz et al, 17 on children with motor deficit. It can be said that, this inconsistencies are due to different research and balance assessment methods and difference in level and severity of subjects' disorder.…”
Section: The Effect Of Strength Training Based On Process Approach Insupporting
confidence: 80%
See 3 more Smart Citations